2016
DOI: 10.1002/joc.4968
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the premonsoon Indian dryline

Abstract: A northeast‐ to southwest‐oriented surface dryline with a dew point gradient of 1 °C per 10 km develops along the eastern Indian coast during the entire premonsoon season. Deep, hot, dry air of up to 500 hPa moves from arid regions in Southwest Asia and Western India to the Bay of Bengal (BoB), and warm, shallow, moist air from the BoB penetrates below the dry air, forming an inclined moisture gradient aloft to the east and reaching the surface to the west. The slope of the gradient depends on the vertically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The low‐level wind at 850 hPa (∼1.4 km) and the potential temperature ( θ ) anomalies averaged from 850 to 700 hPa, shown in Figure 4a, and the 500‐hPa streamline along with relative humidity, shown in Figure 4b, explain the environment in which hot (>7 K on average) and dry (<40% rh) air masses flowing from the north and northwest converge with warm ( θ ∼ 310 K; not shown) and moist (∼90% rh) southwesterlies, embedding Cyclone Roanu. This environment is consistent with that determined in an earlier study (Akter and Tsuboki, 2014; 2017), which showed that, during the premonsoon period, a northerly and northwesterly wind coming from the western arid region was dry and hot, whereas the southwesterly wind over the BoB was warm and moist, leading to a vertically inclined dryline in the north‐northwestern BoB.…”
Section: Environment Around Tcssupporting
confidence: 92%
See 1 more Smart Citation
“…The low‐level wind at 850 hPa (∼1.4 km) and the potential temperature ( θ ) anomalies averaged from 850 to 700 hPa, shown in Figure 4a, and the 500‐hPa streamline along with relative humidity, shown in Figure 4b, explain the environment in which hot (>7 K on average) and dry (<40% rh) air masses flowing from the north and northwest converge with warm ( θ ∼ 310 K; not shown) and moist (∼90% rh) southwesterlies, embedding Cyclone Roanu. This environment is consistent with that determined in an earlier study (Akter and Tsuboki, 2014; 2017), which showed that, during the premonsoon period, a northerly and northwesterly wind coming from the western arid region was dry and hot, whereas the southwesterly wind over the BoB was warm and moist, leading to a vertically inclined dryline in the north‐northwestern BoB.…”
Section: Environment Around Tcssupporting
confidence: 92%
“…During the activity of Cyclone Roanu (2016), the BoB was characterized by an extensive dry–moist environmental contrast, holding less than 60% humidity in the western part of the BoB, as shown in Figure 1c for May 2016. The advection of dry air from the west of the BoB created a prominent nonuniform environmental flow during the premonsoon period (Akter and Tsuboki, 2014; 2017). Conversely, in the case of Cyclone Madi (2013), the entire environment of South Asia, including the BoB, was quite dry, which was examined through relative humidity (rh) data averaged from 950–700 hPa for December 2013 (Figure 1d).…”
Section: Recurving Cyclones Over the Bobmentioning
confidence: 99%
“…This is a natural consequence of the shape of the barrier and of the likely strong temperature contrast between the sea and the intruding, cold, dry air. Lee cyclogenesis is also possible over the Persian Gulf and northern Indian Ocean, however, one notes that this does not occur during the cool, winter season on Earth, because of the presence of subsiding air (Akter and Tsuboki, 2017). However, where cyclogenesis occurs, precipitation would be enhanced, with a concomitant increase in niche amplitude in regions downwind of these barriers.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we should consider two situations. Ahead of the Indian summer Monsoon, near-surface temperatures regularly exceed 40 °C, pressure is relatively low, but there is very limited and sporadic precipitation because the middle and upper troposphere has not responded and the area is overlain by subsiding air (Akter and Tsuboki, 2017). Similarly, over West Africa, the advance of the summer monsoon trough is restricted by prevailing dry, north-easterly winds.…”
Section: Methods and Model Parametersmentioning
confidence: 99%
“…Those that form over the Great Plains of the United States are the most widely studied and are considered as a preferential zone for convection initiation (Wilson and Roberts 2006) which can lead, under favorable conditions, to severe weather events (Lin 2007). Drylines are also found in other regions of the world (Schaefer 1986) like India (Weston 1972;Akter and Tsuboki 2017), eastern China (Golden 1980;Qin and Chen 2017), central West Africa (Hamilton et al 1945), Australia (Arnup and Reeder 2007), and Canada (Taylor et al 2011). In each of these regions, drylines have their own characteristics and development mechanisms, which are strongly linked to local orography and regional synoptic climatology.…”
Section: Introductionmentioning
confidence: 99%